Classroom Challenges of Secondary Level English Teachers at Remote Government Schools in Nepal - Ranjit, Rabu (Journal of Education, Language Innovation, and Applied Linguistics, 2022)
The study was conducted to explore Secondary level English teachers’ classroom challenges in the government schools of remote Nepal. The purpose of the study was to identify classroom challenges of English teachers at the secondary level and analyze how the factors affect English Language Teaching in the classroom. Twenty English teachers responded to the questionnaire, four were selected for the interview and five agreed to participate in focus group discussion. The main findings of the study were; the teachers do not understand students’ local language, overcrowded classrooms, students’ mostly use their native language to communicate, limited lesson hours, students’ poor linguistic background and poor classroom condition. The most interesting finding is that none of the teachers was English graduates. They were from other streams like Major Nepali, Math, Commerce etc. Learning and applying various teaching methods and classroom management techniques, matching students’ linguistic level and the learning situation, making use of time, and self-reflection can help tackle English teachers’ challenges. Keywords: Challenges; English teachers; Government School; Remote; Secondary level.